EFFECTIVE MANAGEMENT OF INFORMATION RESOURCE OF PROJECT-BASED ENTERPRISE - Мандра, Андрей Валерьевич; Пономаренко, Татьяна Викторовна (Eastern-European Journal of Enterprise Technologies, 2013)
The basic mechanisms of the Information Resource (IR) management for the effective functioning of different types of resources of project-based enterprise are proposed. The advantages and disadvantages of the IR for internal innovative environmental development are discussed. Basic methods of personnel training for more rational perception of innovations occurring at a shipbuilding enterprise are described. The main purpose is to analyze the state of information resources of an enterprise, the basic types of resources influenced by IR and to identify the main factors that influence the informational maturity of an enteprise. To analyze the state of IR of the enterprise it is necessary: To determine the level of enterprise maturity (in each direction using maturity models); To identify the gaps of the environment formed; To identify the ways of improving the level of maturity and more effective management of introduction of innovations; To analyze the possibility of improvements on the basis of maturity level determined earlier. Positioning the information resource as one of the most important type of resources is actual in both theoretical and practical aspects to show its role informing the internal innovative environment of an enterprise. These methods do not only determine the strategy of positions listed in the table, in most cases, they are applicable for almost any position that influences the state of information resource in the enterprise and they allow to solve the basic problems of adaptability of the personnel to the conditions of the innovative environment.